Selling Singaporeans on the ISA - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2011)
Assistant Professor of Law Eugene Tan said that allowing judges to review both procedural requirements of preventive detention orders issued under the Internal Security Act would help to bolster public confidence and trust.